Mechanistic-based verification of a structural layer coefficient for high polymer-modified asphalt mixtures. Issue 12 (2nd December 2021) - Habbouche, Jhony; Hajj, Elie Y.; Sebaaly, Peter E.; Piratheepan, Murugaiyah
Abstract : Extensive laboratory performance testing and advanced statistical analyses led to the determination of a fatigue-based structural layer coefficient of 0.54 for high polymer-modified (HP) asphalt concrete (AC) mixtures in new pavements. The objective of this paper was to verify, using mechanistic-empirical (ME) analyses, the structural capacity of HP AC pavement sections designed using the 0.54 layer coefficient. The ME analysis for rutting, shoving, and top-down cracking in the AC layer resulted in most of the cases in a better performance for the HP AC mixes when compared with their respective PMA AC mixes. Moreover, the rut depths determined in the unbound layers were observed to be lower than the maximum allowable rut depth indicating an acceptable performance for the HP pavement sections which had a thinner AC layer thickness. In summary, the verification efforts supported the use of a structural coefficient of 0.54 for HP AC mixes in new pavements.